Analysis The Aspects of Self-Love in a Children's Storybook “Rafa, The Raflesia” - Kasmiati; Wulandari, Suci (International Proceedings of Nusantara Raya, 2022)
Self-love is an ability to appreciate and love yourself as a noble person with weaknesses and strengths that always accompany it. In today's era, humans often have difficulty in treating themselves well and behaving as they are due to various factors. Self-love seems important to be instilled in children from an early age, one of which is through the media of story books, in order to create a strong personality in the future when he grows up. The purpose of this study is to analyze the aspects of self-love in the story book entitled "Rafa, the Raflesia" by Debby Lukita Goeyardi and Vannia Rizky Santoso. This research is a textual-descriptive research, designed using a textual analysis method of a children's story book entitled “Rafa, the Raflesia” through a qualitative approach, namely collecting data through references in the form of books, journals, newspapers, and others similar. The results of the study revealed that in a children's story book entitled “Rafa, the Raflesia” there are four aspects of self-love, namely: 1) self-awareness; 2) self-worth; 3) self-esteem; and 4) self-care. These four aspects will be passed by a child in the process of achieving self-love.